Pengaruh Aspek Keuangan, Kompetensi Sumber Daya Manusia Dan Inklusi Keuangan Tehadap Kinerja Umkm Binaan Rumah Bumn Di Kebupaten Rembang - Linda Febrianti; Siti Alliyah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The study's goal is to prove the impact of monetary aspect, competence in human resources and financial inclusion on the influential UMKM of BUMN di Kab. Rembang. The entire population included in this study UMKM bumn houses in the District Regency Rembang. The sampling technique used simpke random sampling and by using a formula slovin with as many samples 74 respondent. Dta collection was done using questionnaire. The result research shows that variable of financial aspects no signifikan positive effect on the performance UMKM whereas human resource competence what's more, monetary incorporation signifikan positif influence on performance UMKMof BUMN houses in the district regency Rembang.